Clinical and Functional Profile of the elderly residents of a Long-Term Institution from Fortaleza (Research, Society and Development, 2022)
The objective of this study was to identify the clinical-functional profile of elderly residents of a long-term institution using the Functional Clinical Vulnerability Index-20 (IVCF-20). The sample was composed of 29 elderly women, aged 65 and over. The instrument used is composed of 20 questions that contemplate multidimensional aspects of the health condition of the elderly and classifies them as robust, with risk of fragility or fragility. The results obtained in this study categorized mostly elderly women at risk of frailty.